Research on minimum height above ground considering total and ionized field when ± 800 kV power lines at the high altitude cross the residential areas - Guo, Zhijian; Yu, Jian; Wang, Xia; Zhang, Yuexian (Frontiers in Energy Research, 2023)
Recently, in order to reduce carbon emissions and meet climate change targets set by governments worldwide, which has led to the growth of renewable energy sources, such as wind, solar and hydropower energy, more and more ± 800 kV power lines have been built for more than 1500 km long-distance transmission, and the total and ionized field under it serve as important assessment indicators of an electromagnetic field. To calculate the total electric field and ionized field under UHVDC power lines, based on the upwind difference idea proposed by Takuma, the boundary condition and initial value selection are improved with the Kaptzov hypothesis as the boundary condition, and the difference between the surface field strength on the wire and the critical coronal voltage is used as the benchmark to estimate the initial value of charge density. By adopting the improved method, the calculation results of the total electric field and ionized field under the ± 800 kV power lines in typical high altitude regions suggest that the total electric field on the ground increases with the decrease in the wire’s height above ground, while the ion current density goes up with the reduction in the roughness coefficient of the wire; when the ± 800 kV power lines stipulated by national standards go through the residential areas, and the wire’s minimum height above ground is 21 m, total electric field and ionized field under the power lines are less than the limits set by national standards. Also, the calculation method proposed in this paper is suitable for the calculation of ground total electric field for future ± 1,200 kV power lines, which can provide reference for UHVDC power line designing and carbon emission target realization.